FACTORS AFFECTING MENTAL HEALTH ENHANCEMENT OF THE ELDERLY IN MUANG DISTRICT, PHETCHABURI PROVINCE - Pratanvorapanya, Wararat; Sinthusuwan, Jintana; Choeisombat, Penpayom (Journal of MCU Phetchaburi Review, 2023)
The purposes of this research were to 1) study of health promotion factors of the elderly in Muang district, Phetchaburi province, 2) study the mental health level of the elderly in Muang district, Phetchaburi province, and 3) study the factors affecting mental health enhancement of the elderly in Muang district, Phetchaburi province. The sample were 378 elderly in Muang district, Phetchaburi province. The instrument used was a questionnaire. The data were analyzed by using percentage, mean, standard deviation, and stepwise multiple regression analysis. The research results were as follows: 1) the health promotion factors were overall and aspect practiced at a high level. The first aspect is spiritual development, followed by health responsibility, exercise Interpersonal, relationship stress management, and nutrition in last, 2) mental health of the elderly found that most of them have good mental health as other people, representing 53.18 percent, and 3) the health enhancing factors of exercise (X2) and stress management (X6) affect mental health of the elderly with statistical significance at the 0.01 level, prediction efficiency 56.20%, written as a regression equation as follows. = 1.296 + 0.151(X2) + 0.097(X6).